Plume-tectonic scenario of rifting and evolution of the Black Sea megadepression - Kobolev, V.P. (Reports of the National Academy of Sciences of Ukraine, 2016)
The attraction of the plume tectonic mechanism allowed a new position to assess the role of geodynamic factors associated with rifting and evolution of the Black Sea megadepression. A significant difference in the formation mechanism of its main structural units - the western and eastern troughs — is proved. Namely, the primary cause of the western rift depression is the rise of the asthenosphere diapir, leading to a three-prong stretching of individual sections of the Scythian plate. The formation mechanism of the eastern depression involves pushing, i.e. breaking the continuity of the crust and the lithosphere of the Euxinus subcontinental plate. As a result of the deposition rate estimation, it is established that the rifting and the direct formation of the western trough started in the late cretaceous, and the dipping in the area of the eastern trough had began at Eocene.